Community participation in waste management, case study Bang Rak Noi Subdistrict Community Mueang District, Nonthaburi Province - Kongyoungyune , Dr.Pinavet; Kongyoungyune, Dr.Rungradit; Sawadikamthorn , Thakon (Journal of Dhamma for Life, 2024)
The research aimed to study 1) To study the problems and behaviors arising from waste management in the community of Bang Rak Noi Subdistrict, Mueang District, Nonthaburi Province and 2) to study the model of participatory waste management of the people of Bang Rak Noi Subdistrict, Mueang District, Nonthaburi Province. This research is qualitative research. The research tools were interviews and conversations. There were 16 key informants, consisting of 4 village headmen, 4 assistant village headmen, 4 community development volunteers, 4 village health volunteers, and representatives of related organizations, including 1 community developer, 2 subdistrict administrative organization personnel, and the president. Subdistrict Administrative Organization, 1 person, totaling 20 people, is a purposive selection. The results of the research found that 1. The most common problem of villagers in Bang Rak Noi Subdistrict is the problem of bad odor from garbage due to insufficient garbage collection trucks coming into the community. Therefore, there is a problem of accumulation. The problem of inappropriate public garbage disposal points The problem of garbage dumping in the canals, both general garbage and large garbage. Bang Rak Noi Subdistrict's participatory waste management model consists of 1) participation in planning, 2) participation in implementation, 3) participation in evaluation. By the guidelines for waste management by the Bang Rak Noi Subdistrict Administrative Organization. That is, sending officials into community areas to explain so that villagers in the community can learn how to separate garbage and provide appropriate garbage disposal points to wait for garbage collection trucks to come and collect at the next time.